2018
DOI: 10.14527/pegegog.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative and hindering factors regarding the supervisory relationship based on supervisors’ and undergraduate supervisees’ opinions

Abstract: The purpose of the present study was to examine Turkish counseling supervisors’ and undergraduate supervisees’ opinions about the supervisory relationship. Upon completion of Individual Counseling Practice course, semi-structured individual interviews were conducted with four voluntary supervisors (two female and two male) and their four voluntary undergraduate supervisees (four female) in a case study design. Content analysis results revealed three main categories of supervisors’ and supervisees’ opinions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
1
9
0
10
Order By: Relevance
“…The problems of the trainees regarding the supervision are lack of communicating with the supervisor, negative attitudes of the supervisor and audio-recording of the sessions. These results seem to be consistent with previous research (Büyükgöze-Kavas, 2011;Hill et al, 2007;Meydan, 2019;Meydan & Denizli, 2015;Özteke-Kozan, 2018). The results are also in line with the second phase of Rønnestad and Skovholt's (2003) therapist/counselor development model: beginning student phase.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
“…The problems of the trainees regarding the supervision are lack of communicating with the supervisor, negative attitudes of the supervisor and audio-recording of the sessions. These results seem to be consistent with previous research (Büyükgöze-Kavas, 2011;Hill et al, 2007;Meydan, 2019;Meydan & Denizli, 2015;Özteke-Kozan, 2018). The results are also in line with the second phase of Rønnestad and Skovholt's (2003) therapist/counselor development model: beginning student phase.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
“…For instance, supervisor disclosure (Knox et al, 2008;Knox et al, 2011;Ladany & Lehrman-Waterman, 1999;Ladany et al, 2001) and encouragements for disclosure (Nelson et al, 2008) facilitate the supervisee disclosure. Additionally, Turkish first-time supervisees generally expect their supervisors to be polite, relieving, caring, humorous, supportive/encouraging, sincere, understanding, soothing, fair, helpful, and respectful (Aladağ, 2014;Meydan, 2019;Meydan & Denizli, 2018;Meydan & Koçyiğit, 2019) and to use interventions such as disclosure, open-ended questions, active listening, supportive confrontation (Meydan, 2019;Meydan & Denizli, 2018;Meydan & Koçyiğit, 2019). In this context, it could be asserted that the supervisor is important for first-time supervisees in several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Meydan and Denizli (2018), first-time supervisees reported that as basic developmental need, they needed to be supported about their clinical issues and as intermediate developmental need to discuss their personal issues in supervision meetings. In another study (Meydan, 2019), first-time supervisees noted that both supervisors' some interventions, personal characteristics and their own attitudes toward supervision and personal characteristics could affect the supervisory relationship.…”
Section: The Purpose Of the Studymentioning
confidence: 99%
“…Benzer şekilde süpervizyon ilişkisinin sadece süpervizor ve aday psikolojik danışman arasındaki ilişki olarak algılanmaması gerektiği, danışanın da süpervizyon ilişkisine etkileri olduğu ve aday psikolojik danışman tarafından süpervizyon ortamına bu etkinin taşındığı düşünülmektedir (Meydan ve Koçyiğit-Özyiğit, 2016). Bununla birlikte aday psikolojik danışmanların ve süpervizörlerin; süpervizyon ilişkisine dair görüşleri kolaylaştırıcı faktörler, zorlaştırıcı faktörler ve etkiler olmak üzere üç tema altında toplandığı görülmektedir (Meydan, 2019). Süpervizyon sürecinde süpervizörlerin ve aday psikolojik danışmanların görüşlerinin süreci anlamlandırmak için oldukça önemli olduğu söylenebilir.…”
Section: Introductionunclassified